Risk Factors for Distant Metastasis in Patients with Minimally Invasive Follicular Thyroid Carcinoma - Lee, Yu-Mi (PLoS One, 2016)
BACKGROUND: Although patients with minimally invasive follicular thyroid carcinoma (MIFTC) generally have an excellent prognosis, distant metastasis occurs in some patients. Risk factors for distant metastasis have been reported, none has been found to be conclusive. This study evaluated risk factors for distant metastasis, including protein markers, in patients with MIFTC. METHODS: A review of patient records identified 259 patients who underwent surgery at Asan Medical Center from 1996 to 2010 and were subsequently diagnosed with MIFTC. After review of pathological slides, 120 patients with paraffin blocks suited for tissue microarrays (TMA) were included in this study. Immunohistochemical stain of TMA slides was performed by protein markers; β-catenin, C-MET, CK19, estrogen receptor (ER) α, ER β, HBME-1, MMP2, PPAR γ and progesterone receptor. RESULTS: 120 patients included 28 males (23.3%) and 92 females (76.7%), of mean age 41.5±10.8 years (range, 13–74 years). Eight patients (6.7%) had distant metastases during follow-up. Univariate analysis showed that age (≥45 years), male sex, and extensive vascular invasion (≥4 foci) were associated with distant metastasis. Multivariate regression analysis showed that extensive vascular invasion was the only independent risk factor for distant metastasis (p = 0.012). Although no protein markers on TMA analysis were directly related to distant metastasis of MIFTC, CK19 expression was more frequent in patients with than without extensive vascular invasion (p = 0.036). CONCLUSION: Extensive vascular invasion was the only independent risk factor for distant metastasis of MIFTC. No proteins markers were directly related to distant metastasis, but CK19 was associated with extensive vascular invasion.